Ad hedificandum ibi domum: Santa María de Vallbona, its Foundation, and First Construction (History Journal «Jerónimo Zurita», 2023)
The documents from the female Cistercian Monastery of Santa María de Vallbona (Vallbona de les Monges, Urgell, Lleida), have been published and are well known. However, these documents have not yet been interpreted in the light of unresolved issues concerning its foundation and the initial building and decorative processes. As such, one of the aims of this paper is to stress the importance of the historiographic controversy around Cistercian nuns de iure/sine iure to shed some light on the debate surrounding the eremitic or royal foundation of the monastery and its adoption of the Cistercian rule. Further, the architectural setting and its sculptural decoration are analysed for issues such as the female identity of the monastic community, its main female artistic sponsors and donors, and the liturgical use of its different spaces.
Keywords: Cistercian Monasteries; Crown of Aragon; Vallbona de les Monges; Female Medieval Monasticism; Architecture; Sculpture